Imaginary worlds: Karl May and the refugees - Linhard, Tabea Alexa (Patterns of prejudice, 2023)
Linhard's article shows how the imaginary worlds of German pulp author Karl May (1842-1912) appear in the memories of Jewish and anti-fascist refugees who found asylum in the Americas. Yet the refugees were not the only ones who had once been avid readers of May's fictions: his novels were just as appealing to supporters of fascism, even, some claim, to Hitler himself. May's novels are built on racialized and gendered imaginaries that made them equally suitable for those who saw indigenous cultures in the Americas as ultimately inferior and in need of guidance from the European characters, and those who brought with them romantic visions of still racialized, yet benevolent and noble natives. These visions bear no relationship to indigenous cultures in Latin America and instead are transposed from beliefs and tropes about the 'Indians' featured in the adventures of Winnetou and Old Shatterhand. Writers forced into exile, among them Leo Spitzer, Klaus Mann, Gertrude Duby and Egon Erwin Kisch, wrote about the ways in which reading May shaped how they once saw the Americas. The traces of May's influence in the writings of displaced Jews and anti-fascists reveal a certain blindness to colonial racism that, while characteristic of the times when these authors came of age, was still part of world-views that many were not ready to challenge. Understanding the impact of the work of a man who called his novels 'travel narratives' (even though he never visited the places he claimed to be writing about) brings us one step closer to understanding more about the inner lives of Holocaust refugees in the colonial world.